Prognostic Value of Elevated Pre-treatment Serum CA-125 in Epithelial Ovarian Cancer: A Meta-Analysis - Wang, Qingyi; Feng, Xiaoling; Liu, Xiaofang; Zhu, Siyu (Frontiers in Oncology, 2022)
Background CA-125 is a clinical biomarker with predictive effect on the prognosis of different cancers. Numerous clinical trials have been conducted to investigate the possibility of using the pretreatment level of CA-125 to predict the prognosis of epithelial ovarian cancer (EOC). However, its value in predicting prognosis remains controversial. The purpose of this meta-analysis was to assess the predictive value of pretreatment CA-125 levels for prognosis in EOC patients. Methods We searched the EMBASE, Cochrane library, PubMed and Web of Science databases for studies published up to 3 December 2021, according to specific inclusion and exclusion criteria. The clinical studies that were included investigated the relationship between pretreatment CA-125 levels and ovarian cancer prognosis. Combined hazard ratios (HR) of overall survival (OS) and progression-free survival (PFS) reported in the studies were compared and analyzed using fixed-effects/random-effects models. Sensitivity analysis was used to assess study stability, while Egger’s and Begg’s tests were used to assess publication bias. Results This meta-analysis included 23 studies published in 2004 - 2021 with a total of 10,594 EOC patients. Comprehensive analysis demonstrated that the serum level of CA-125 before treatment was significantly correlated with overall survival (OS: HR=1.62, 95%CI=1.270-2.060, p<0.001) and progression-free survival (PFS: HR=1.59, PFS: HR=1.59, 95%CI=1.44 1.76, p<0.001). After comparing data from different FIGO stages and treatments, we discovered that a high pre-treatment serum CA-125 level was associated with a low survival rate. Conclusion According to the results of this study, a higher pre-treatment serum CA-125 level is associated with poor survival outcomes, which can be utilized to predict the prognosis of EOC patients. Pre-treatment serum CA-125 level might provide reliable basis for predicting the risk of EOC disease progression. This study is registered with the International Prospective Register of Systematic Reviews (CRD42022300545). Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=300545, identifier [CRD42022300545].